Development of truss finite element analysis software using ANSYS - Nurul Farhana, Mohamad (2010)
Truss is one of the important components for a structure and need to be designed in such a way that they have enough strength and rigidity to satisfy the strength and serviceability limitation. Although there are many existing commercial engineering software such as STAAD.Pro, LUSAS, MATLAB and etc, but most of them are expensive and it is hard for those small companies to get the license easily. Finite Element analysis has been reported to be suitable tool to analysis the truss. This is because finite element analysis is cheaper and easier to conduct compared to full scale test. Here, the study was conducted to prove finite element analysis using nonlinear analysis is able to give a similar result as the lab test. This report presents the development of truss finite element analysis software using ANSYS. The purpose of this study is to develop a cheaper home-grown truss analysis software using ANYS. A stepby-step Finite Element formulation of simple truss is discussed and Graphical User Interfaces (GUTs) was developed so as to provide user-friendly environments. At the end of the study, results generated from the truss analysis software are compared with the existing engineering software STAAD.Pro. for validation.